2007
DOI: 10.1093/jxb/erl290
|View full text |Cite
|
Sign up to set email alerts
|

A mutational approach to the study of seed development in maize

Abstract: The maize seed comprises two major compartments, the embryo and the endosperm, both originating from the double fertilization event. The embryogenetic process allows the formation of a well-differentiated embryonic axis, surrounded by a single massive cotyledon, the scutellum. The mature endosperm constitutes the bulk of the seed and comprises specific regions containing reserve proteins, complex carbohydrates, and oils. To gain more insight into molecular events that underlie seed development, three monogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Rather than reviewing every mutation, we will discuss selected mutations that in our opinion provide crucial insight. There are a number of publications that contain a wealth of information about mutations affecting endosperm development in cereals (Jarvi and Eslick, 1975;Nelson, 1980;Neuffer and Sheridan, 1980;Satoh and Omura, 1981;Bosnes et al, 1987;Kowles et al, 1992;Scanlon et al, 1994;Kurata et al, 2005;Dolfini et al, 2007).…”
mentioning
confidence: 99%
“…Rather than reviewing every mutation, we will discuss selected mutations that in our opinion provide crucial insight. There are a number of publications that contain a wealth of information about mutations affecting endosperm development in cereals (Jarvi and Eslick, 1975;Nelson, 1980;Neuffer and Sheridan, 1980;Satoh and Omura, 1981;Bosnes et al, 1987;Kowles et al, 1992;Scanlon et al, 1994;Kurata et al, 2005;Dolfini et al, 2007).…”
mentioning
confidence: 99%
“…An increasing number of genes have been shown to affect aleurone and general surface specification in maize, uncovering identity mechanisms based on the proper membrane localization and recycling of kinase-type receptors and signal processors (Becraft and Asuncion-Crabb, 2000; Kessler et al, 2002), whose effect is aleurone-specific at the cellular level but affects the whole seed development. The size reduction, common to the previously commented category, indicates the relevance of the surface tissues to properly complete endosperm filling (Dolfini et al, 2007). A point of further interest in these lines is the mutation's effect on other plant epidermal tissues, as common developmental routes have been discovered along the years (Lid et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…We validated their use as indicators of presence/state of development of a specific tissue in qRT-PCR by comparing the relative values obtained in the analysis of upper (formed by aleurone and starchy endosperm) and lower (aleurone, starchy endosperm, transfer cells and ESR) halves of WT seeds. Previous studies through Northern blot and in situ hybridization have shown that these BETL and ESR transcripts are undetectable by these techniques in the upper endosperm, while aleurone and starchy endosperm markers distribute approximately evenly (Hueros et al, 1999; Gómez et al, 2002; Balandín et al, 2005; Muñiz et al, 2006; Dolfini et al, 2007). The differences in the values obtained are in all cases in agreement with previous data, showing over 1 order of magnitude difference in their accumulation in bottom over the top half for the basal specific genes, while those expressed in the aleurone and starchy endosperm are roughly comparable in both samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant emb8516 is produced by an insertion in the ZmPRPL35 gene, which encodes a plastid ribosomal protein (Magnard et al, 2004;Ma et al, 2004). Mutant empty pericarp2 (emp2) is the result of an insertion in a gene encoding a heat shock binding protein (HSBP1) (Fu et al, 2002), while empty pericarp4 has an insertion in a gene which encodes a protein containing a pentatricopeptide repeat, located in the mitochondria and possibly involved in the regulation of expression of a small subset of mitochondrial transcripts in the endosperm (Dolfini et al, 2007;Gutierrez-Marcos et al, 2007).…”
Section: B Amentioning
confidence: 99%